The Urgency Of Regulating Foreign Bribery Crime In Indonesia:Constitutional Legal Framework Analysis - Rodiyah, Rodiyah; Asyaffa Ridzqi Amandha; Indah Sri Utari; Anis Widyawati (Pandecta Research Law Journal, 2025)
The focus of the research is on the urgency of regulating foreign bribery crime in Indonesia aswell as the Indonesian constitution perspective. This issue raises concerns, because theregulation of foreign bribery crime has not been included in Indonesian Laws, makingIndonesia a country that cannot follow up on this criminal act. The questions that arise are 1)what the urgency of the regulation of the law on foreign bribery crime in Indonesia is is 2)what the perspective of the Indonesian constitution regarding foreign bribery crime is is. Thepurpose of this study is to describe the urgency of legal regulation of the concept of foreignbribery crime in Indonesia, and the perspective of the Indonesian constitution regardingforeign bribery crime. The research method uses juridic-normative research with a qualitativeapproach to law. The results of the research show that 1) Indonesia is a participating countryof UNCAC and has ratified it through Law Number 7 of 2006. However, until now there is noregulation to criminalize foreign bribery. In fact, according to the researcher, this is an urgencybecause the opportunity for variation in corruption cases but not followed by criminal reformof the criminal offense, resulting in the enforcement of corruption crimes is not optimal. 2) TheIndonesian Constitution, by adopting Foreign Bribery in Indonesian legislation, it is hoped thatIndonesia can enforce its laws fairly